Penerapan Strategi Make a Match dalam Meningkatkan Hasil Belajar pada Materi Durus al-Lughah: Tanfīdz Istirātījiyyati Make a Match Litarqiyati Natāij Al-Ta’līm fī Mādati Durūs Al-Lughati Al-‘Arabiyyati - Ahmad Kali Akbar; Rahma, Nisa Nur (Tarling : Journal of Language Education, 2024)
State Junior High School 5 Ngawi is a public educational institution for the preparatory stage, regulated by the Ministry of Education, which specializes in the understanding of Islamic religion and incorporates the teaching of the Arabic language into its curriculum. However, there are still many problems in teaching the Arabic language, resulting in students' performance remaining low, below the average set by the curriculum standards. This is attributed to the lack of student engagement in the learning process, as evidenced by their lower activity levels in learning, reduced interest in the teacher's explanations throughout the teaching process, and a sense of boredom during the learning process. This is a result of the teacher's limited creativity in selecting methods, strategies, or resources that can support the teaching process. Therefore, the researcher aims to provide solutions for learning using the "Make A Match" strategy to enhance activity and learning outcomes for eighth-grade students (Grade H) at State Junior High School 5 Ngawi. Based on the mentioned educational issues, the research objectives are as follows: firstly, to investigate the enhancement of learning activity for eighth-grade students (Grade H) using the "Make A Match" teaching strategy in the Arabic language subject. Secondly, to explore the improvement of learning output for eighth-grade students (Grade H) using the "Make A Match" teaching strategy in the Arabic language subject at State Junior High School 5 Ngawi.